Minor Dynasties to the West and East of Baghdad - Chaerul Andi Sakri; A. Muhammad Batara; Umar Sulaiman (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the small dynasties that emerged in the western and eastern regions of Baghdad during the Abbasid Caliphate. Using a qualitative descriptive method and a literature study approach, this research collects data from various literature sources such as books, journals, and relevant articles. The analysis is carried out through stages of reduction, categorization, and interpretation of the collected literature. The main focus of this study is on the basic principles of developing teaching materials that are relevant to the curriculum, effectiveness, efficiency, as well as theoretical approaches in the fields of education, language, and teaching material development. The small dynasties that emerged as a result of political disintegration in the 10th century demonstrate how local groups such as the Persians and Turks established dynasties like the Tahirid, Saffarid, and Samanid in the eastern region of Baghdad, and the Idrisid, Aghlabid, and Tulunid in the western region of Baghdad. Although most of these dynasties did not last long, they played an important role in maintaining regional stability and introducing semi-autonomous governance that connected peripheral regions with the center of the caliphate. This study is expected to provide a deeper understanding of the political dynamics during the disintegration of the Abbasid Caliphate and its contribution to the development of Islamic civilization at that time.